THE RELATIONSHIP BETWEEN NURSES' CARING BEHAVIOR AND INPATIENT SATISFACTION LEVEL AT DR. REKSODIWIRYO CLASS III HOSPITAL, PADANG IN 2025 - Hamdani, Hamdani; Oresti, Syalvia; Dorisnita, Dorisnita (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Nurses’ caring behavior is a fundamental component of nursing services that significantly influences inpatient satisfaction. Patient satisfaction is a key indicator of healthcare service quality in hospitals. This study aimed to determine the relationship between nurses’ caring behavior and inpatient satisfaction at RS TK. III Dr. Reksodiwiryo Padang in 2025. This study employed a quantitative analytical design with a cross-sectional approach. The population consisted of all inpatients at RS TK. III Dr. Reksodiwiryo Padang, with a total sample of 89 respondents selected using accidental sampling. Data were collected using validated questionnaires measuring nurses’ caring behavior and patient satisfaction. Data analysis was conducted using univariate and bivariate analyses with the Chi-Square test. The results showed that 53 respondents (59.6%) perceived nurses’ caring behavior as caring, and 69 respondents (77.5%) reported being satisfied with nursing services. The Chi-Square test revealed a p-value of 0.000 (p < 0.05), indicating a significant relationship between nurses’ caring behavior and inpatient satisfaction. In conclusion, nurses’ caring behavior has a significant association with inpatient satisfaction. Hospitals are encouraged to strengthen caring behaviors through continuous training and professional development to improve nursing service quality and patient satisfaction.